Identifying the existence of workplace bullying : a study among working students of ICCE - Anis Faizal bin Mohd Fatoni (Kulliyyah of Education, International Islamic University Malaysia, 2019)
Workplace bullying is a problem and is an important organisational and social concern. This study examined workplace bullying and the awareness of the ICCE students on the issue. The research showed how the students respond to or are aware of the existence of bullying in their workplace. Workplace bullying is difficult to identify and contained because harassments usually take place covertly, many times out of sight of supervisors and coworkers. The central findings of this study covered: (a) the demographic frequency involved, (b) existing working environment and relationship, (c) specific types of mistreatment that occur, and (d) support and action taken pertaining to the issue. The data in this study found the percentage of participants reported of witnessing mistreatment of coworkers sometime throughout their careers, the percentage of those who have been bullied during their career, and a portion of it who have admitted to being a target of a bully in the last 12 months. This study also examined the frequency of cases being reported by the participants. Although the sample is limited, findings suggest that employees perceive their organisational environment to be filled with abusive bosses, coworkers and negative acts that should be a cause for concern.